Strategi Pengelolaan Layanan Administrasi Sarana dan Prasarana Laboratorium IPA pada SMK Negeri Kota Lubuklinggau - Destrianto Faisal; Rudi Erwand; Ahmad Gawdy Prananosa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to describe the management strategies of administrative services for science laboratory facilities and infrastructure at SMK Negeri 1, SMK Negeri 2, SMK Negeri 3, and SMK Negeri 4 Lubuklinggau City. The method used was a qualitative approach with a descriptive method. Data collection techniques were conducted through interviews, observations, and documentation studies. The research informants consisted of school principals, vice principals for facilities and infrastructure, laboratory heads, laboratory assistants, and science teachers. The results show that the management strategies of science laboratory administrative services include planning the needs for facilities and infrastructure, organizing the duties of laboratory managers, implementing orderly and systematic administrative services, and conducting periodic supervision and evaluation. Several obstacles were identified, including limited budgets, a lack of laboratory assistants, and suboptimal utilization of facilities and infrastructure. In conclusion, the management strategy of science laboratory administrative services needs to be carried out in a planned, organized, and sustainable manner through effective coordination and the use of administrative technology to improve the effectiveness of laboratory services in schools. Keywords: Laboratory Administration, Facilities and Infrastructure, Management Strategy